Quality of life of patients with end-stage peritoneal metastasis treated with Pressurized IntraPeritoneal Aerosol Chemotherapy (PIPAC). Issue 10 (October 2015) - Odendahl, K.; Solass, W.; Demtröder, C.; Giger-Pabst, U.; Zieren, J.; Tempfer, C.; Reymond, M.A.
Abstract Background Quality of Life (QoL) plays an important role in patients with peritoneal metastasis and is deteriorating continuously until death. Pressurized Intraperitoneal Aerosol Chemotherapy (PIPAC) is an innovative palliative treatment of peritoneal metastasis. We present the first QoL results under PIPAC therapy. Methods Retrospective analysis of QLQ30 questionnaire results during repeated courses of PIPAC applications in palliative patients with pretreated peritoneal metastasis. Results 91 patients (M:F = 40:51, median age 64 (34–77) years) with 158 PIPAC applications were analyzed. 86% patients had previously received systemic chemotherapy. Peritoneal metastasis was advanced (Peritoneal Carcinomatosis Index I = 16 ± 10). At admission, only moderate impairment of functioning (62–83%) and symptom scores (17–47%) was observed. 48 patients received at least 2 PIPAC every 6 weeks. After PIPAC # 1, the global physical score deteriorated slightly (from 82% to 75%), but improved after PIPAC # 2 (up to 89%). Gastrointestinal symptoms (nausea/vomiting, constipation, diarrhoea, anorexia) remained stable under PIPAC therapy. Conclusions Quality of life was relatively high in this group of patients with advanced, pretreated peritoneal metastasis, explaining their wish for further therapy. Functioning scores and disease-related symptoms were not altered for at least 3 months in the patients able to receive repeated PIPAC. Except for a transient moderate increase of pain scores, PIPAC did not cause therapy-related QoL deterioration, especially no gastrointestinal symptoms.